Cleft Constructions in Public Speeches and in Fiction - Čaladi, Marek (Univerzita Pardubice, 2012)
The aim of this paper is to describe cleft constructions in public speeches and in direct speech in fiction. The paper is divided into two parts. The theoretical part provides a description of English word order and sentence elements, their structure and main functions. After that, it deals with two main types of cleft constructions, namely cleft sentences and pseudo-cleft sentences and their structure and functions are described. In the practical part, an analysis of a linguistic corpus is conducted based on the theoretical knowledge discussed in the first part of the paper. Overall occurrence and major tendencies of the use of cleft constructions in both functional styles are observed and commented on.
Vytýkací konstrukce ve veřejných projevech a v beletrii
Keywords: vytýkací konstrukce; it-cleft; wh-cleft; vytknutý člen; aktuální větné členění; cleft construction; it-cleft; wh-cleft; highlighted element; functional sentence perspective